Sea, River, Lake Ice Properties and Their Applications in Practices - Li, Zhijun; Kolerski, Tomasz; Zhou, Li; Shi, Xiaohong; Zhang, Zhengyong; Li, Fang (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint covers topics on geographical scale of glacier and lake ice variations, as well as the engineering scale of ice properties and their practical applications via laboratory tests and numerical modeling.